2016
DOI: 10.1111/aji.12491
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Natural Cytotoxicity Receptors on and Intracellular Cytokine Production by NK Cells in Women with Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is characterized by glucose intolerance that is caused by metabolic changes during pregnancy, and is considered a risk factor for the occurrence of DM in future. There are studies that reported changes in the cytokine in women with GDM. The concentration of serum IFN-γ and adiponectin decreased, while serum leptin, IL-6, IL-10, and TNF-α increased in GDM women when compared to that in healthy pregnant women. 16 17 Placenta and adipose tissues from patients with GDM releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 60 publications
(81 reference statements)
2
23
0
1
Order By: Relevance
“…Hara et al found lower number of circulating NK cells in GDM, but did not analyze the percentage of cell subpopulations according to the level of CD56 expression. In contrast and in line with our results, Chiba et al observed higher percentage of CD56 dim cells and lower of NK CD56 bright cells in pregnant women with GDM.…”
Section: Discussionsupporting
confidence: 92%
“…Hara et al found lower number of circulating NK cells in GDM, but did not analyze the percentage of cell subpopulations according to the level of CD56 expression. In contrast and in line with our results, Chiba et al observed higher percentage of CD56 dim cells and lower of NK CD56 bright cells in pregnant women with GDM.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, we have demonstrated the importance of NKp46 in reproduction. We have reported decreased expression of NKp46 in peripheral blood in women with previous reproductive failures, such as RPL and implantation failure, in peritoneal fluid in women with pelvic endometriosis, and in peripheral blood in pregnant women with gestational diabetes mellitus . These studies suggest that regulation of NKp46 expression in various types of NK cells may be one of the key factors in reproductive failure.…”
Section: Discussionmentioning
confidence: 73%
“…We have reported decreased expression of NKp46 in peripheral blood in women with previous reproductive failures, such as RPL and implantation failure, 16,26,27,34,35 in peritoneal fluid in women with pelvic endometriosis, 36 and in peripheral blood in pregnant women with gestational diabetes mellitus. 37 These studies suggest that regulation of NKp46 expression in various types of NK cells may be one of the key factors in reproductive failure. Additionally, analysis of NKp46 expression may be a useful tool to investigate and diagnose reproductive failures, such as RPL and implantation failure.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that hyperglycaemia leads to an inflammatory condition associated with increased expression of cytotoxic cells. Chiba et al in a prospective study showed higher percentages of cytotoxic NK, lower frequencies of cytokine‐secreting NK cells and NKCD56 bright /NKp46 + in the diabetic patients compared to the controls. They also found increased IFN‐γ‐ and TNF‐α‐producing CD56 + cells and decreased TGF‐β and VEGF‐producing CD56 + cells in GDM patients.…”
Section: Immune Cellsmentioning
confidence: 99%